Problems facing civic education as a means of promoting democratic governance in future adults for national development and cohesion - Ibe, P. C.; Ogbunugwor, A. U.; Chukwuma, F. O. (Journal of Research in Adult and Continuing Education, 2023)
The problem of achieving national development and cohesion is one of the major challenges facing Nigeria today. Lack of national cohesion has had a lot of negative impacts in the society. Obviously, the nation faces a lot of problems such as unstable democratic governance, dearth of popular participation which is a pillar to democracy, religious and cultural intolerance, disunity, negligence of human rights and its value. National development and cohesion cannot exist in the presence of the above problems. Consequently, this article is to create awareness on the impact civic education could have on tackling the above mentioned ills of the nation by promoting democratic governance.This study examined civic education as a means of promoting democratic governance to ensure national development and cohesion and highlighted several problems confronting its implementation in Nigeria. The meanings of national development, national cohesion and civic education were presented and it purposes/aims were outlined. Effort was also made to provide the meaning of democratic governance and, roles of civic education in promoting democratic governance. The researchers recommended among others that; government should make civic education a compulsory subject/course from primary to higher institutions in Nigeria in order to instill the right attitudes, values and civic responsibilities in the students as future adults.  Conclusively, civic education is very crucial in creating active citizens willing to participate and contribute to democratic governance which will promote sustainable national development and cohesion.
Keywords: National development; national cohesion; civic education; democratic governance; sustainability; problems